Translation of oral health research priorities into research topics in an equity-based priority setting exercise - Sumanth Nagraj Kumbargere; Cath Quinn; Lynne Callaghan; Martha Paisi; Mona Nasser (Health Research Policy and Systems)
Abstract Background In the context of research priority-setting, participants express their research priorities and ideas in various forms, ranging from narratives to explicit topics or questions. However, the transition from these expressions to well-structured research topics or questions is not always straightforward. Challenges intensify when research priorities pertain to interventions or diagnostic accuracy, requiring the conversion of narratives into the Participant, Intervention, Comparator, Outcome (PICO) format. Scope and findings This project aimed to understand the challenges of engaging a diverse, multilingual population in setting oral health research priorities. While not a comprehensive priority-setting effort, we modified James Lind Alliance’s (JLA) methods and used thematic analysis to establish a list of priority research topics and questions. This was accomplished by conducting interviews with 40 community participants and 14 dentists from various ethnic backgrounds in Malaysia. The interview language depended on participant preferences, including English, Malay, and Mandarin, with translations handled collaboratively by bilingual research assistants. The process involved thematic analysis, discussion with a research committee, and necessary modifications. Our interpretations revealed distinct categories of participant statements: explicit, complicated, implicit and incomplete. In this study, we identified a three-step approach to translate research ideas that are presented either as explicit statements or as complicated narratives. Conclusions Translating community research priorities poses inherent challenges. Our model, although not exhaustive, provides a valuable tool to assist research priority-setting groups in translating these priorities into meaningful research topics and questions, facilitating the equitable inclusion of diverse perspectives. Future research priority-setting endeavours should document their translation processes, thus aiding researchers in understanding and tackling the intricacies of this task.